2005
DOI: 10.1098/rsif.2005.0066
|View full text |Cite
|
Sign up to set email alerts
|

A review of attenuation correction techniques for tissue fluorescence

Abstract: Fluorescence intensity measurements have the potential to facilitate the diagnoses of many pathological conditions. However, accurate interpretation of the measurements is complicated by the distorting effects of tissue scattering and absorption. Consequently, different techniques have been developed to attempt to compensate for these effects. This paper reviews currently available correction techniques with emphasis on clinical application and consideration given to the intrinsic accuracy and limitations of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
112
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 86 publications
0
112
0
1
Order By: Relevance
“…It can be predicted that the development of the spectral correction technique 11 will promote the classi¯cation accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…It can be predicted that the development of the spectral correction technique 11 will promote the classi¯cation accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that subtracting the reflectance from the fluorescence or dividing the two parameters provides similar net NADH changes. Very recently, Bradley and Thorniley (20) published a review article dealing with the various correction techniques for tissue fluorescence. They summarized their review by the following conclusion: "even though research has been conducted into correction techniques for over thirty years, the development of a successful and practical correction technique remains a considerable challenge.…”
Section: Monitoring Devices and Technological Aspectsmentioning
confidence: 99%
“…We have found that subtracting the reflectance from the fluorescence or dividing fluorescence over reflectance provides similar net NADH changes. In 2006, Bradley and Thorniley 55 reviewed the available techniques for correction of fluorescence signals. They concluded, "even though research has been conducted into correction techniques for over thirty years, the development of a successful and practical correction technique remains a considerable challenge.…”
Section: Monitoring Of Nadh: History Principles and Basic Technologymentioning
confidence: 99%